A STUDY OF INFLATION DYNAMICS IN INDIA - Rahul Singh, Bibhor Kumar, Subhanjani Yadav (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper focuses on examining the drivers of inflation and its component in India using monthly data from January 2013 to December 2019. CPI-(Combined) as a measure of inflation is considered for analysis along with their component. It has been declared as the new standard for measuring inflation since April 2014 and changes in the CPI is used to measure its rate of inflation. Based on findings of the study, there is a long run relationship between all measures of inflation and its determinants. The results on FEVD suggest that maximum variation in inflation is explained by crude oil inflation, then by exchange rate and monetary factors. Least variation is explained by food inflation. All the determinants significantly Granger Cause CPI inflation.